Assumptions in Decision Making Scholarship: Implications for Business Ethics Research - Martin, Kirsten; Parmar, Bidhan (2012)
While decision making scholarship in management has specifically addressed the objectivist assumptions within the rational choice model, a similar move within business ethics has only begun to occur. Business ethics scholarship remains primarily based on rational choice assumptions. In this article, we examine the managerial decision making literature in order to illustrate equivocality within the rational choice model. We identify four key assumptions in the decision making literature and illustrate how these assumptions affect decision making theory, research, and practice within the purview of business ethics. Given the breadth of disciplines and approaches within management decision making scholarship, a content analysis of management decision making scholarship produces a greater range of assumptions with finer granularity than similar scholarship within business ethics. By identifying the core assumptions within decision making scholarship, we start a conversation about why, how, and to what effect we make assumptions about decision making in business ethics theory, research, and practice. Examining the range of possible assumptions underlying current scholarship will hopefully clarify the conversation and provide a platform for future business ethics research.
Keywords: Teaching Business Ethics; Intuitions; Dual-processing; Sensemaking; Constructionism; Objectivism; Decision Making